2021
DOI: 10.1108/ijoem-02-2021-0258
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of frugal innovation for firms in emerging markets: the roles of leadership, knowledge sharing and collaborative culture

Abstract: Purpose Due to the vital role of frugal innovation (FI) for firms in developing and emerging economies, the purpose of this study is to investigate the effect of transformational leadership (TL) and knowledge sharing (KS) on FI of firms in supply chains. This study aims to bring deeper insight on the correlation among the constructs by exploring and analyzing the moderating effect of collaborative culture (CC) in the KS-FI relationship. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(113 citation statements)
references
References 63 publications
1
84
0
Order By: Relevance
“…The leaders of SMEs could utilize social networking to help with strategic decision-making ( Hyypiä and Khan, 2018 ). Previous studies evaluated the moderating impact of collaborative culture ( Le, 2021 ), market and technological turbulence ( Dost et al, 2019 ), and bricolage ( Iqbal et al, 2021a ) on the “sustainable leadership-frugal innovation” relationship. Thus, this study considers the research gap based on situational leadership theory by examining the impact of managerial ties on frugal innovation, especially among SMEs in sustainable leadership.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leaders of SMEs could utilize social networking to help with strategic decision-making ( Hyypiä and Khan, 2018 ). Previous studies evaluated the moderating impact of collaborative culture ( Le, 2021 ), market and technological turbulence ( Dost et al, 2019 ), and bricolage ( Iqbal et al, 2021a ) on the “sustainable leadership-frugal innovation” relationship. Thus, this study considers the research gap based on situational leadership theory by examining the impact of managerial ties on frugal innovation, especially among SMEs in sustainable leadership.…”
Section: Introductionmentioning
confidence: 99%
“…A close association with competitors can initiate firms to conduct information exchange and inter-firm collaboration. This idea will ultimately reduce implicit collusion ( Li et al, 2014 ), a critical factor in frugal innovation ( Le, 2021 ). Furthermore, communication with managers promote sharing of technology and knowledge ( Li et al, 2008 ; Wang and Chung, 2013 ), fostering collaboration with different stakeholders ( Wu and Peng, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Fischer et al (2021) suggested that we could refer to green goods and renewable processes as eco-innovation. Le (2021) described the FI as “hardware or software advancement in association with green processes and products, including advanced technology involved in saving energy, avoidance of emissions, composting, green products development, organizational environment management. Innovative application at all levels.” Innovative technologies, environmental pollution control, recycling, green product design, and ecological management are key FI priorities ( AlMulhim, 2021 ; Hossain et al, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Innovation capabilities are the main source of innovative knowledge and information from external and internal stakeholders [39]. Organisations obtain advantages of novel ideas by formulating the latest procedures and techniques for designing products and services [40]. Alternatively, frugal innovation is a means by which business firms can use available resources for innovation activities and processes [41].…”
Section: Mediates Through Frugal Innovationmentioning
confidence: 99%